Experimental and numerical characterization of harbor oscillations in the port of Málaga, Spain - Sammartino, Simone; Sánchez Garrido, José C.; Delgado-Cabello, Javier; Naranjo-Rosa, Cristina Belén; Criado-Aldeanueva, Francisco; García Lafuente, Jesús (Elsevier, 2014)
The port of Málaga is routinely affected by short period sea level oscillations whose amplitudes, typically of few cm, can sporadically outweigh the tidal variations. High frequency oscillations in the innermost basins may cause problems of stability of the moored crafts. This motivated the characterization of the resonant behavior of the port and its response to external forcing, which has been carried out by experimental and numerical approaches. The Helmholtz mode of the harbor has been found at 16.5- min period, in both observed data and numerical experiments. A second mode of period around 6–7 min, beyond the temporal resolution of the tide gauge, has been detected only in the numerical results. The typical scenario during the occurrence of harbor oscillations is a low atmospheric pressure (75% of the cases) with noticeable content of high frequency pressure disturbances, a situation that is quite commonly observed during the transit of atmospheric fronts across the Iberian Peninsula. Winds appear to be of secondary influence, even when the oscillations are preferably observed under westerlies. Although results are not conclusive, resonance mechanisms (Proudman and Greenspan resonance) for transferring energy from the atmosphere to the ocean are proposed as the physical process generating the harbor oscillations.
Keywords: Puertos; Harbor resonance; Sea level oscillations; Resonance modes; MITgcm